Neutrophil elastase and endogenous inhibitors in Behçet's disease saliva. (29th July 2020) - Novak, T.; Fortune, F.; Bergmeier, L.; Khan, I.; Hagi‐Pavli, E.
Summary: Behçet's disease (BD) is a vasculitis of unknown aetiology typified by chronic recurrent oral ulcers and systemic inflammatory manifestations. Neutrophils, and specifically their protease neutrophil elastase (NE), have been implicated in its pathology. Although NE is an effective anti‐microbial, excessive NE can damage host tissue. Recurrent oral ulceration is a primary BD symptom, therefore we hypothesized that excessive neutrophil infiltration evidenced by increased NE and a reduction in specific endogenous inhibitors, secretory leucocyte protease inhibitor (SLPI) and alpha1‐anti‐trypsin (α1AT) contributes to BD mucosal instability. NE, SLPI and α1AT were quantified in saliva from BD patients with active oral ulcers (BDa) and quiet without ulcers (BDq), recurrent aphthous stomatitis (RASa; RASq) and healthy controls (HC). Although BDq saliva had marginally higher median NE levels (1112 ng/ml) compared to both RASq (1043 ng/ml) and HC (999 ng/ml), SLPI was significantly reduced in BDq ( P < 0·01). Despite decreased SLPI protein, mRNA expression was significantly increased in BDq buccal epithelial swabs compared to RASq and HC ( P < 0·05, P < 0·001). NE remained enzymatically active, although α1AT levels were at least eight times higher than SLPI in all groups, suggesting that α1AT does not have a primary role in counteracting NE in saliva. Furthermore, NE levels in BDa patients medicated with both azathioprine (AZA) and colchicine (COLC) were significantly lower than those on COLC ( P = 0·0008) or neither ( P = 0·02), indicating that combining AZA + COLC may help to regulate excessive NE during ulceration. This study showed that enzymatically active NE coupled with reduced SLPI in BD saliva may contribute to recurrent oral ulcerations. Abstract : Recurrent oral ulcers and hyperactive blood neutrophils are characteristic of Behҫet's Disease (BD). High levels of enzymatically active neutrophil elastase (NE) were measured in saliva of BD patients without ulcers (BDq), which can lead to extracellular matrix degradation and mucosal instability. BD oral epithelial cells expressed high levels of secretory leukocyte protease inhibitor (SLPI) mRNA, however, salivary SLPI protein was depleted. Although high levels of salivary alpha‐1 antitrypsin (α1AT) were detected, NE was not fully inhibited. We propose that BDq individuals experience a protease‐anti‐protease imbalance in favour of NE which may contribute to their recurrent oral ulceration episodes.